Phosphorus Removal by Electric ARC Furnace Steel Slag Adsorption - Lee, Kah Fei (2017)
As to overcome and control the arising environmental issue – eutrophication in lakes and reservoirs the resulted from excessive input of phosphorus (P) due to rapid urbanization and uncontrolled agriculture activities. Electric are Furmace Stell Slag (EAFS), a steelmaking by-product, rather than dispose this industrial waste which is economically unfavourable, it’s physical and chemical properties exhibits high potential to be great P adsorbent. The objectives of this study was to investigate the effect on phosphorus removal efficiency and P removal capacity by EAFS adsorption through variation of parameters such as pH, size of slag and initial concentration of phosphorus and to identify most suitable mathematical model in description of adsorption by using traditional batch experiment. Results demonstrated that, Langmuir is suitable in describing P-removal mechanisms model with the Maximum Adsorption Capacity, Qm of 0.166 mg/g and Langmuir Constant, KL of 0.03519 L/mg . While small size of adsorbent shows higher percentage (up to 37.8%) of P=removal compared to the larger size. Besides that, the experiment showed a more acidic environment is favourable for P-removal and the amount of P adsorbed at pH 3.0 was the highest. In addition, the adsorption capacity increases steadily as the initial P concentration increase but is remained steady at 100mg P/L. Eventually this study should help in better preliminary understanding on P removal mechanisms by EAFS.